Simplicity in agile software development - SANTOS, Wylliams Barbosa (2018)
The study of simplicity is an interdisciplinary endeavour with many concepts and attributes, challenger in defining, development and use. Several studies emphasise that the concept of simplicity is, in itself, by far not a simple concept because there are many perspectives on the perception of simplicity. Agile Software Development (ASD) has proven to be an important set of methods in promoting simplicity issues. However, there are difficulties in defining simplicity and its impact on IT development and use. This study presents a theory to foster the simplicity phenomena to improve agile software development. Additionally, this thesis focuses on understanding how project managers and software engineers interpret their experiences, considering the simplicity issues in agile software development. The research method used in this work is based on the principles of Evidence-Based Software Engineering. It is stated as basic (research outcome), inductive (research logic), exploratory and descriptive (research purpose), interpretivist (research approach), qualitative (research process), basic qualitative study (research methodology), literature review and interviews (data collection methods), grounded theory techniques and thematic analysis (data analysis methods). A set of categories (lightweight process, knowledge acquisition, effective communication, time consuming, and transparency) that affect the simplicity in agile software development were grounded. Finally, the categories and hypotheses with higher explanatory power were used to create the substantive theory about simplicity in agile software development. The results show that a better understanding of the implications of simplicity on agile software development may contribute to the projects’ success.